FEATURES OF THE RESEARCH WORK ELEMENTS DEFORMABILITY OF RAILWAY TRACK - Bondarenko, I. O. (Science and Transport Progress, 2015)
Purpose. The scientific paper is supposed the determination of basic physical and structural conditions in modeling life cycle of the elements of the railway line for the study of deformation processes as the basis of normative base of the track at the condition of railway safety. Methodology. To achieve the aim principles of the elasticity theory and wave propagation process in the description of the interaction between the track and rolling stock were used. Findings. The basic physical and structural conditions under which it is necessary to carry out the simulation of the life cycle of the elements of the railway line for the study of deformation processes were determined. The basic physical and structural principles of drawing the design schemes of railway track elements for the process assessment of the track deformation work were formulated. The decision correctness and the possibility of the problem solution are proved. Originality. The study of the track reliability questions motivates the development of new models, allow considering it for some developments. There is a need to identify the main physical and structural conditions for assembly design schemes based on assessment and prediction of possible track state changes during its operation. The paper presents the basic principles of physical and structural drafting design schemes of railway line items for which Huygens’ principle is implemented. This principle can be performed only when the four dimensional space: the volume changing over time is considered. Practical value. Analytical models applied in determining the parameters of strength and resistance lines, fully satisfy the task, but can not be used to determine the parameters of track reliability. One of the main impossibility factors of these models is quasidynamic approach. Therefore, as a rule, receive and examine not only dynamic process of a railway track, but also its consequences. Besides, these models are related to flat ones, and it also adds some complexity in results comparing with an experiment, as well as the process is not easy to distinguish the impact of volume in its limited parts. The use of numerical methods extend the posibilities, and it also make it impossible for the consideration of the dynamic process, as well as it is impossible to introduce processes, causing the reaction to stress load. Thus the basic physical and constructive approaches in modeling make it possible to consider the dynamic process of localized both in time and in space directly.